How do you factor by grouping 5n^2 + 19n + 12?

3 Answers
May 9, 2018

=> (5n+4)(n+3)

Explanation:

Factor by grouping? This is just normal factoring, no grouping is needed:

5n^2+19n+12 = (5n+4)(n+3)

If you want to use factoring by grouping anyway, then you have to break up the middle term with n into pieces that sum to 19n in total.

=(5n^2+15n) + (4n + 12)

=5n(n+3) + 4(n+3)

=(5n+4)(n+3)

May 9, 2018

(5n+4)(n+3)

Explanation:

When we do factoring by grouping, we want to split the b term (coefficient on n) into two terms so we can factor two separate expression.

5n^2+color(blue)(19n)+12 can be rewritten as

5n^2+color(blue)(15n+4n)+12

Notice, the blue terms are equivalent, so I didn't change the meaning of this expression.

Now, we can factor!

color(red)(5n^2+15n)+color(lime)(4n+12)

We can factor a 5n out of the red expression, and a 4 out of the green expression. We get

color(red)(5n(n+3))+color(lime)(4(n+3))

which can be rewritten as

(5n+4)(n+3)

Hope this helps!

May 9, 2018

Use an AC method to split the middle term, then factor by grouping to find:

5n^2+19n+12 = (5n+4)(n+3)

Explanation:

Given:

5n^2+19n+12

Use an AC Method to find the split we need.

Look for a pair of factors of AC = 5 * 12 = 60 with sum B=19.

The pair 15, 4 works in that 15 * 4 = 60 and 15+4=19.

Using this pair to split the middle term, we can then factor by grouping:

5n^2+19n+12 = (5n^2+15n)+(4n+12)

color(white)(5n^2+19n+12) = 5n(n+3)+4(n+3)

color(white)(5n^2+19n+12) = (5n+4)(n+3)